Answer:
Part I : Eliminating x terms
Step 1: There are two equations. To eliminate the x terms we have to make similar x-terms in both the equation.
Step 2: Cancel x- terms by using addition or subtraction of 2 equations.
Step 3: Find the value of y and substitute into any equation and find the value of y
Part II : Eliminating y terms
Step 1: There are two equations. To eliminate the y terms we have to make similar y-terms in both the equation.
Step 2: Cancel y- terms by using addition or subtraction of 2 equations.
Step 3: Find the value of x and substitute into any equation and find the value of x
The value of (x,y) = (-4.5, -10)
Explanation:
It is given that,
2x-3y=21 -----(1)
-6x+2y=7 -------(2)
To find the value of x and y
Eliminating x terms:-
(1) ⇒ 2x-3y = 21
(1) * 3 ⇒ 6x - 9y = 63 -----(3)
Adding eq(2) and eq(3)
-6x + 2y = 7 -------(2)
6x - 9y = 63 -----(3)
--------------------------------
-7y = 70
y = 70/-7 = -10
Substituting the value of y in eq(1)
eq(1) ⇒2x - 3y = 21
2x - 3 *(-10) = 21
2x + 30 = 21
2x = 21 - 30 = -9
x = -9/2 = -4.5
Therefore the value of (x,y) = (-4.5, -10)